Os efeitos da aplicação dos royalties petrolíferos sobre as finanças públicas dos municípios brasileiros - Reis, Diego Araújo (2013)
Changes occurred with the enactment of Law 9478 of 1997, led to some municipalities a financial condition inside, due to the higher inflow of royalties from oil and natural gas. The increase in revenue from royalties from oil and natural gas also ran on the other hand, the extraordinary expansion of the oil sector and the escalation of international prices of raw materials. The sum of these features plus a recipe mean expressive, is an important opportunity to expand investment and to meet the social demands. Royalties are derived from the operation of a nonrenewable resource, which implies that it has a period of exhaustion. For this reason, the literature stresses that his application should be made in capital and human capital. The overall goal of this dissertation is to analyze what were the purposes of royalties on public finances of the federal entities in the period from 1999 to 2011. From the methodology were characterized variables analysis. The analysis model was adopted panel data, which combines cross-sectional data with time series. Based on the tests, it was found that the counties most dependent on royalties increased capital expenditures with increased royalties, both from the perspective as the proportion per capita tax. For personnel costs, it was noted that these were influenced by royalties per capita in all municipalities. Moreover, from the perspective of tax ratio, the tests showed that the more dependent counties, showed a negative relationship. With regard to expenditure on education and culture, it was noted that royalties per capita influenced its formation in considerable part of the municipalities. However, in addressing the proportion fiscal few municipalities were affected, while in the cities most dependent inverse relationship exhibited. As for social spending on health, sanitation, housing and urban development was seen that some of these municipalities increased spending on the inflow of royalties. Finally, in the area of environmental expenditures, only the counties most dependent on royalties increased their spending with increased use.